Evidence update: GlaxoSmithKline's inactivated quadrivalent influenza vaccines. (1st February 2016) - Bekkat-Berkani, Rafik; Ray, Riju; Jain, Varsha K; Chandrasekaran, Vijayalakshmi; Innis, Bruce L
ABSTRACT: Inactivated trivalent influenza vaccines (IIV3s) are designed to protect against illness caused by two influenza A virus subtypes and one influenza B virus lineage. They may provide inadequate protection due to the co-circulation of viruses from two antigenically distinct influenza B lineages. Incorporating strains from both B lineages as in inactivated quadrivalent influenza vaccines (IIV4s) reduces this risk. We summarize the evidence supporting two IIV4s manufactured by GSK Vaccines. Compared to IIV3s, these two IIV4s demonstrated noninferior immunogenicity against the shared influenza strains and superior immunogenicity for the strain of the additional B lineage, particularly in subjects who were seronegative for that B strain. One IIV4's efficacy in children aged 3–8 years was 55.4% against influenza of any severity and 73.1% against moderate-to-severe influenza. Both IIV4s were well-tolerated with a similar safety profile to IIV3s. These IIV4s are more likely than IIV3s to protect against the added influenza B strain.